Joy Milk Bar Sdn. Bhd. / Normazlina Ahmad ... [et al.] - Ahmad, Normazlina; Moktar, Nurulhuda; Abdul Aziz, Nurul Zulfa; Mohd Akhir, Norirna; Madzlan, Amir Amri (Faculty of Hotel and Tourism Management, 2004)
JOY MILK BAR SDN BHD is a special name for our company. Joy means our product spread happiness for people who buy and drink our special drinks. Milk means all off our drinks product are made base on milk item. Bar means a place that sells drinks where the server stands to do the service and people always gather and having a discussion or chat with each other.